Rice Technology and Production - Fahad, Shah (IntechOpen, 2017)
Rice is life, for most people living in Asia. Rice has shaped the cultures, diets, and economies of thousands of millions of people. Growing, selling, and eating rice are integral to the culture of many countries. Products of the rice plant are used for a number of different purposes, such as fuel, thatching, industrial starch, and artwork. Rice is the staple food of more than half of the world's population - more than 3.5 billion people depend on rice for more than 20% of their daily calories. Asia accounts for 90% of global rice consumption, exceeding 100 kg per capita annually in many countries. Keeping in view the importance of rice, the United Nations declared 2004 as the International Year of Rice. Food security, which is the condition of having enough food to provide adequate nutrition for a healthy life, is a critical issue. Sustainable rice production is important for food self-sufficiency and food security in changing climates. Sustainable rice production practices are those which (1) increase rice productivity and its quality, (2) improve soil fertility and health, (3) increase water use efficiency and conservation, and (4) increase diversification of rice fields, growers' income, and climate resilience.